129I and 236U distribution in the subpolar North Atlantic unravels water mass provenance in AR7W and A25 lines - Lisa G. T. Leist; Maxi Castrillejo; John Norton Smith; Marcus Christl; Christof Vockenhuber; Antón Velo; Pascale Lherminier; Núria Casacuberta; Núria Casacuberta (Frontiers in Marine Science, 2024)
The subpolar North Atlantic (SPNA) is crucial in the global ocean circulation system and one of the few regions where deep convection occurs. The intermediate and deep waters formed in the SPNA have long been investigated, yet their sources and pathways are not fully understood. In this study, we employ a combination of two radionuclide tracers, namely, 129I and 236U, to understand water mass provenance and mixing in the SPNA. The concentrations measured between Portugal and Greenland and across the Labrador Sea in 2020/2021 agreed with previously observed tracer distributions. The highest tracer concentrations were measured in the East Greenland Current (EGC), Denmark Strait Overflow Water (DSOW), and, to a lesser extent, in the eastward-flowing Labrador Sea Water (LSW). In contrast, waters of southern origin such as the North East Antarctic Bottom Water and North East Atlantic Central Water (ENACW) carried comparably smaller amounts of 129I. By using a binary mixing model, we estimated that the EGC contains about 29%–32% of the Polar Surface Water outflowing the Fram Strait. DSOW was mainly derived from 20% to 35% Return Atlantic Water and mixed with LSW. The Iceland Scotland Overflow Water (ISOW) evolved into North East Atlantic Deep Water in the Irminger and Labrador seas primarily by mixing with LSW and, to a lesser extent, with DSOW. The 129I and 236U binary mixing approach was less conclusive for LSW, reaching the current limitation of the model. This study suggests potential benefits and limitations of using 129I and 236U to investigate the mixing and provenance of water masses in the SPNA.